PENGELOLAAN KEUANGAN DAN PENGEMBANGAN USAHA PADA USAHA MIKRO KECIL MENENGAH (STUDI KASUS PADA UMKM MADU HUTAN LESTARI SUMBAWA) - Muhammad Sabiq Hilal Al Falih; Reza Muhammad Rizqi; Nova Adhitya Ananda (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2019)
This study aims to determine the financial management and business development applied to Sumbawa Sustainable Forest Honey MSMEs. The analytical method used is a descriptive qualitative method. Technic analysis consists of three activity lines that occur simultaneously, namely data reduction by collecting data through interviews with the informants concerned with research, after that in presenting data collection of information that has been obtained and then arranged in accordance with the theoretical foundation used then make conclusions and taking action, the last is verification of data, in verifying the data the author uses data triangulation techniques. The results of the study show how financial management and business development are implemented by MSMEs, namely the behavior of financial management that is still simple, seen from the way the financial records do not meet the standards, while in developing business opportunities the strengths and opportunities of MSMEs are quite large, this is seen from the analysis of IFAS and IFAS factors obtained through SWOT analysis, after obtaining opportunity points of 0.80, threat 1.20, strength of 1.60 and weakness of 1.10 UMKM positions in courtesies diagrams occupying IV quadrant positions namely diversification into strategy what must be done is to maintain customer or customer satisfaction, by improving service, quality, promotion and innovation. improve product quality to compete with other honey.